2014
DOI: 10.1037/a0037141
|View full text |Cite
|
Sign up to set email alerts
|

Little evidence for links between memory complaints and memory performance in very old age: Longitudinal analyses from the Berlin Aging Study.

Abstract: Cross-sectional and longitudinal relationships between memory complaint and memory performance were examined in a sample of old-old participants from the Berlin Aging Study (BASE; N = 504, ages 70 to 100, age M = 84.7 at study onset). Participants were measured 4 times over the course of 6 years. Similar to many previous studies, initial cross-sectional memory complaints were predicted by depression and neuroticism, but not memory performance. Subjective age also predicted memory complaint independent of other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
91
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(100 citation statements)
references
References 111 publications
(166 reference statements)
8
91
1
Order By: Relevance
“…Perhaps longitudinal data minimize the effect of variables that influence self-concept but are unrelated to memory status, thereby enhancing the validity of reported changes in memory as an indicator of actual memory change. However, some longitudinal studies examining correlated changes have found nil to small associations [7,14,18] , consistent with cross-sectional metaanalyses. The reasons for discrepant longitudinal findings are not yet clear and might be based on methodological differences (e.g., nature of the population, age of the sample, measure of memory complaints vs. memory ratings).…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…Perhaps longitudinal data minimize the effect of variables that influence self-concept but are unrelated to memory status, thereby enhancing the validity of reported changes in memory as an indicator of actual memory change. However, some longitudinal studies examining correlated changes have found nil to small associations [7,14,18] , consistent with cross-sectional metaanalyses. The reasons for discrepant longitudinal findings are not yet clear and might be based on methodological differences (e.g., nature of the population, age of the sample, measure of memory complaints vs. memory ratings).…”
Section: Introductionmentioning
confidence: 78%
“…However, one novel outcome in this study was the larger relation of actual memory change to change in subjective memory for persons high in depressive symptoms. This outcome could indicate that individuals experiencing dysphoria are more realistic and more concerned about their changing memory [7] . Conversely, this outcome could be framed as maintenance of a positive evaluation of one's own mem-ory functioning in face of cognitive declines -a self-protective strategy that is less likely to occur for those experiencing higher levels of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations